The Influence of the Cooperative Learning Model of the Think Pair Share (TPS) Type Using Index Card Match on Students' Mathematics Learning Outcomes - Noviyanti, Dina; Angraini, Lilis Marina; Wahyuni, Astri; Nurjanah, Nurjanah (International Journal of Contemporary Studies in Education, 2025)
Purpose - This study aimed to determine the effect of the Think Pair Share (TPS) cooperative learning model using Index Card Match on the mathematics learning outcomes of class X students of SMAN 1 Pekaitan on the material of three-variable linear equation systems. Methodology - The research method applied is a quasi-experiment with a Nonequivalent Control Group Design. The sample in this study consisted of 2 groups, namely the experimental group and the control group. Class X3 as the experimental group, consisting of 30 students and class X1 as the control group, consisting of 26 students. The instrument in this study was a post-test of mathematics learning outcomes, which was analysed using the Independent Sample Test with the help of the SPSS 25 application program. Findings - The results of the study showed a value of 0.004, meaning that the value was significant because the value was <0.005. From the test results, there was a difference between the experimental class group and the control class group. Novelty - This research is important to do because mathematics is still often considered difficult. The use of the Think Pair Share (TPS) cooperative learning model using Index Card Match is very necessary because it can improve student activity, conceptual understanding, and student learning outcomes. Significance - Therefore, this research helps teachers choose new ways to achieve learning objectives. It can be concluded that the use of the Think Pair Share (TPS) cooperative learning model using Index Card Match has an effect on the mathematics learning outcomes of class X students at SMAN 1 Pekaitan.